The Influence of Academic Supervision by the School Principal on Teacher Performance at SMPN 1 Baitussalam, Baitussalam District, Aceh Besar Regency in 2024 - Roslina Roslina; Rahmattullah Rahmattullah; Rita Novita (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This study investigates the influence of academic supervision conducted by school principals on teacher performance at SMPN 1 Baitussalam, located in Baitussalam District, Aceh Besar Regency, in the year 2024. Academic supervision plays a pivotal role in the realm of educational management, aiming to enhance the quality and effectiveness of teaching and learning. This research utilizes a literature review methodology, examining a range of scholarly articles, educational theories, and empirical studies related to the impact of leadership on instructional practices. The analysis reveals that effective academic supervision is directly linked to improvements in teacher performance. Key components of successful supervision include the provision of constructive feedback, regular performance assessments, and opportunities for professional development. The study highlights that principals who actively engage in the supervisory process foster a collaborative learning environment, which not only motivates teachers but also encourages them to adopt innovative teaching strategies that enhance student learning outcomes. Furthermore, the research addresses contextual factors, such as school culture, the principal’s leadership style, and the availability of resources, which significantly affect the effectiveness of academic supervision at SMPN 1 Baitussalam. The findings suggest that tailored training programs and a supportive institutional framework can significantly bolster teacher performance. This paper concludes with practical recommendations for school leaders, emphasizing the necessity of implementing structured academic supervision practices that prioritize teacher development. Ultimately, this study underscores the essential role of academic supervision in improving educational quality, enhancing teacher effectiveness, and fostering a positive school culture.